Variations in the northern permafrost boundary over the last four decades in the Xidatan region, Qinghai-Tibet Plateau - Luo, Jing; Niu, Fu-jun; Lin, Zhan-ju; Liu, Ming-hao; Yin, Guo-an (Journal of Mountain Science, 2018)
The distribution and variations of permafrost in the Xidatan region, the northern permafrost boundary of the Qinghai-Tibet Plateau, were examined and analyzed using ground penetrating radar (GPR), borehole drilling, and thermal monitoring data. Results from GPR profiles together with borehole verification indicate that the lowest elevation limit of permafrost occurrence is 4369 m above sea level in 2012. Compared to previous studies, the maximal rise of permafrost limit is 28 m from 1975 to 2012. The total area of permafrost in the study region has been decreased by 13.8%. One of the two previously existed permafrost islands has disappeared and second one has reduced by 76% in area during the past similar to 40 years. In addition, the ground temperature in the Xidatan region has increased from 2012 to 2016, with a mean warming rate of similar to 0.004A degrees C a-1 and similar to 0.003A degrees C a-1 at the depths of 6 and 15 m, respectively. The rising of permafrost limit in the Xidatan region is mainly due to global warming. However, some non-climatic factors such as hydrologic processes and anthropic disturbances have also induced permafrost degradation. If the air temperature continues to increase, the northern permafrost boundary in the Qinghai-Tibet Plateau may continue rising in the future.